Enhancing Students' Reading Comprehension in Narrative Text Using Story Mapping Strategy - Albiansyah, Albiansyah; Minkhatunnakhriyah, Minkhatunnakhriyah (Jurnal Bahasa Inggris, 2020)
This study was a classroom action research that deals with story mapping strategy usage in enhancing the reading comprehension of students in narrative text. The aim of the study was to reveal the implementation of this strategy in learning narrative, and also to explain the understanding of reading after using the classroom story mapping strategy. The participants were all grade VIII.5 students of SMP Negeri 1 Tembilahan Hulu. The qualitative data collection methods used an observation sheet, an interview, and a field note. The quantitative is a test. It is noticed on the basis of data analysis that story mapping strategy improved the comprehension of reading in the narrative text by students. In cycle 1 and cycle 2, the changes occurred. The reading comprehension enhancement for students in cycle 1 was 60.3 (enough) to 77.4 (good) in cycle 2. The outcome indicates that for grade VIII.5 students, the use of the story mapping strategy is an effective strategy in improving the students’ comprehension of reading a narrative text. The variables that modify student enhancement depending on the interview and observation outcomes reflect the excitement of students when using story mapping sheets in the story mapping strategy.